Incremental shuttle walking is associated with activation of haemostatic and haemorheological markers in patients with coronary artery disease: the Birmingham rehabilitation uptake maximisation study (BRUM). Issue 11 (17th March 2005) - Lee, K W; Blann, A D; Ingram, J; Jolly, K; Lip, G Y H
Abstract : Objective: To test the hypothesis that an incremental shuttle walk test (ISWT) affects plasma indices of endothelial damage and dysfunction (von Willebrand factor (vWf)), platelet activation (soluble P-selectin), thrombogenesis (D-dimer), fibrinogen, and plasma viscosity more adversely in coronary artery disease (CAD) than in health. ISWT is a standardised walking test that provokes maximal performance and correlates strongly with maximum oxygen uptake. Methods: Research indices were measured before a practice ISWT and immediately after the second ISWT in 53 patients with CAD (48 men, mean (SD) age 59 (10) years) and in 19 matched healthy controls (16 men, 61 (10) years). Data were analysed before and after ISWT. Results: Despite no significant difference in total distance walked between patients and controls, vWf (162 (45) before v 170 (48) UI/dl after) and fibrinogen (2.9 (0.7) v 3.1 (0.7) g/l) concentrations, plasma viscosity (1.63 (0.12) v 1.71 (0.14) mPa·s), and D-dimer (0.20 (interquartile range 0.10–0.30) v 0.21 (0.12–0.31 mg/l; all p < 0.05), but not soluble P-selectin, were significantly increased after ISWT in patients with CAD, even after correction for plasma volume change. Only fibrinogen (2.5 (0.7) v 2.7 (0.7 g/l) and plasma viscosity (1.60 (0.08) v 1.64 (0.08) mPa·s; both p < 0.01) increased among controls. The increment of fibrinogen was significantly higher in patients than in controls (p  =  0.035) and correlated with total walking distance ( r  =  0.46, p < 0.001) and peak heart rate ( r  =  0.28, p  =  0.02). The increment of plasma viscosity rise also significantly correlated with total distance walked ( r  =  0.66, p < 0.001). Conclusions: ISWT in patients with CAD appears to increase fibrinogen, vWf, and D-dimer compared with healthy controls.